Analisis Pengendalian Kualitas Produk Plastik Menggunakan Metode DMAIC pada PT Techpack Asia - Syafiq Tian Maulana (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2026)
Product quality is one of the determining factors of a company's competitiveness in the cosmetic packaging manufacturing industry. This research was conducted at PT Techpack Asia to address the problem of high product defect rates (spot scrap) caused by the presence of airborne particles measuring 1 micron and 5 microns in the K1 and K2 production areas. This study employed an observational descriptive quantitative approach by applying the DMAIC (Define, Measure, Analyze, Improve, Control) method. Data collection was carried out through measurements at 27 points using a particle counter before and after General Cleaning (General Cleaning / GC) activities. The results showed that airborne particles have a significant influence on spot defects in the final product. The implementation of improvements through the General Cleaning process proved effective in significantly reducing the number of particles in the K2 area. However, cleaning in the K1 area was still not optimal, as indicated by persistently high scrap rates. The use of control charts is recommended to monitor particle trends as part of continuous quality improvement efforts.